Larangan Pemakaian Emas Bagi Laki Laki (Studi Hadis Dalam Tinjauan Sains) - Nasution, Akmal; Is, Fadhilah (Kutubkhanah, 2025)
This research aims to examine the prohibition on wearing gold for men from a hadith perspective and review its health implications. In Islam, the use of gold by men is prohibited based on several hadiths of the Prophet Muhammad SAW. Through a qualitative approach, this study analyzes hadiths related to this topic and reviews relevant health literature to understand the potential impact of gold use on men's health. The results of the hadith analysis show that this prohibition is based on several authentic traditions which firmly state that gold and silk are forbidden for Muslim men. From a science perspective, although gold is generally considered inert and safe, some studies have shown that wearing gold jewelry can cause allergic reactions, contact dermatitis, and potential electromagnetic interference in the body. Allergic reactions and contact dermatitis occur due to individual sensitivity to certain metals, while electromagnetic influences still require further research for a more comprehensive understanding.This research concludes that the prohibition on wearing gold for men in Islam is not only based on theological reasons but also has significant health implications. A deeper understanding of these religious teachings can provide additional benefits in the context of the physical well-being and health of the people.